Development of IRES-incorporated lactococcal bicistronic vector for gene delivery into eukaryotic cells - Abdul Mutalib, Nur Elina (2016)
Internal ribosome entry sites (IRES) are viral RNA elements associated with the construction of bicistronic or polycistronic vectors for the expression of multiple genes in an eukaryotic system due to its ability to initiate translation of mRNA internally.Currently, lactic acid bacteria (LAB) and their vectors have been garnering attention for their prospective applications similar to their E. coli counterparts. However, lack of available lactococcal vectors, especially for heterologous protein production in eukaryotes is a glaring factor for its underwhelm utilization in research. In addition, available reported lactococcal eukaryotic vector only enabling single gene insertion into the vector, thus allowing only one protein to be produced, although it is a common knowledge that functional proteins from eukaryotes were normally assembled from two or more subunits. The aim of this study focused on the incorporation of IRES and other eukaryotic elements in lactococcal vector, pNZ8048 to drive dual genes expression in eukaryotic cells. The lactococcal-based bicistronic vector was cloned with the VP2 gene of infectious bursal disease virus (IBDV) and a gene encoding green fluorescent protein (GFP) and denoted as pNZ:VIG. The functionality of the bicistronic vector was tested by analyzing co-translation of the VP2 and GFP proteins. The vector was subjected to in vitro coupled transcription and translation cell-free system, transient transfection into chicken embryo fibroblast, DF1 cells, and bacteria mediated plasmid transfer using Lactococcus lactis as the bacteria carrier. Cell-free lysate extracts incubated with the newly developed vectors showed the presence of 49 kDa and 29 kDa protein bands corresponding to the relative molecular weight (Mr) of VP2 and GFP proteins, respectively, when subjected to SDS PAGE and Western blotting.Transient expression from in vitro DNA transfection into DF1 cells was verified with positive detection of green fluorescence emission due to the GFP production and a 49kDa band corresponding to the Mr of the VP2 protein detected from the proteins extracted from transfected DF1 cells. Prior to bactofection, the cell wall of L. lactis was weakened with glycine and lysozyme treatment to increase the efficiency of plasmid transferred from L. lactis into DF1 cells. Bactofection analysis showed that the plasmid in L. lactis can be transferred into DF1 cells and the genes cloned in the plasmid can be transcribed and translated. Protein band relative to the Mr of VP2 protein was detected via SDS PAGE and Western blotting profile and green fluorescence was detected using fluorescence microscope. The cell wall treatment of L. lactis with glycine and lysozyme in this study was shown to increase the plasmid transfer efficiency based on the intensity of the bands detected on the Western blot membrane. Conclusively, the results in this study indicated the ability of the bicistronic lactococcal vector to perform co-expression of two genes delivered via in vitro DNA transfection and bactofection thus, making it feasible for expression of other antigenic or therapeutic genes for vaccine and beneficial proteins delivery into eukaryotes.